Activity and selectivity behavior of 1,2-epoxyethylbenzne hydrogenation in carbon dioxide solvent - Rode, Chandrashekhar V.; Hiyoshi, Norihito; Mine, Eiichi; Shirai, Masayuki (Industrial & Engineering Chemistry Research, 2009)
Catalytic hydrogenation of 1,2-epoxyethylbenzene to 2-phenylethanol over charcoal-supported noble metal in carbon dioxide was studied, and the results were compared with those in heptane and methanol. Charcoal-supported palladium and platinum (Pd/C and Pt/C) catalysts were active metal species for the hydrogenation in solvents. The order of activities over palladium and platinum was heptane < carbon dioxide < methanol; however, the formation of dehydroxylated byproduct was suppressed in carbon dioxide solvent. Negative carbon dioxide pressure effect was observed over the Pd/C and Pt/C catalysts in the carbon dioxide solvent.

Active sites in modified copper catalysts for selective liquid phase dehydration of aqueous glycerol to acetol - Mane, Rasika B.; Yamaguchi, Aritomo; Malawadkar, Atul V.; Shirai, Masayuki; Rode, Chandrashekhar V. (RSC Advances, 2013)
We report here the influence of oxides of various metals viz. Ba, Mg, Zr, Zn, Al, and Cr in modified copper catalysts, on the formation of different copper species and acid sites responsible for dehydration of aqueous glycerol to acetol. These catalysts were prepared by a co-precipitation method, among which the catalysts having higher acid strength and predominant Bronsted acidity (Cu-Mg, Cu-Zr and Cu-Al) gave the highest acetol selectivity (76-92%), while the catalysts with lower acidity such as Cu-Zn showed very poor (25%) selectivity to acetol in spite of the highest conversion of 68%. Nevertheless, catalysts exhibiting higher activity and acetol selectivity also showed the presence of metallic Cu confirmed by XRD and XANES-EXAFS characterization. Based on these results, two different catalytic pathways have been proposed highlighting the role of Lewis and Bronsted acidity along with the metal sites in individual steps of glycerol dehydration reaction.